Monitoring Land Use Changes Using Remote Sensing and Geographical Information System (GIS) in Gua Musang, Kelantan, Malaysia - Senthavy, Somkhit (2000)
The development of land use is rapidly changing due to economic improvements. The availability of the most recent land use information is very useful and necessary for administration, monitoring and management for decision making and planning. With advanced technology of remote sensing (RS) and geographical information system (GIS), the mapping process can acquire spatial information more efficiently, timely and easy to recheck. This study was undertaken to detect land use change by integrating RS and GIS technologies in northern part of Gua Musang district, Kelantan state. The objective of this study was to assess the usefulness of integrating remotely sensed data with GIS for land use change detection. The specific objective is to quantify and map the land use change in northern part of Gua Musang district. In order to acquire land use changes data, a set of Landsat Thematic Mapper (TM) dated May 1990 and July 1997 with scale of 1:150,000 in hard copies were acquired. Land use classes were interpreted into maps and the maps were checked on the field for ground truth. The land use map data were then transferred directly into the computer via ARC/INFO and ARCNIEW software. The land use data were digitized in ARC/INFO, overlaid and analyzed in ARC/VIEW. Ground result showed that the total overall map accuracy was 86.54%. Shrub (bushy/lalang) increased by 181.14% from 1990 to 1997 (13,757.35 ha), while newly cleared areas, rubber, and oil palm increased by 91.37% (402.48 ha), 45.19% (6,791.68 ha) and 44.72% (7,81 2.66 ha), respectively. On the other hand, other land use classes such as mixed horticulture, diversified crops, urban and paddy also increased by 38.82% (327.27 ha), 11.95% (71.95 ha), 10.30% (73.63 ha) and 4.70% (12.79 ha) respectively. However, undisturbed and disturbed forest were reduced by 8.10% (19,271.35 ha) and 27.70% (9,978.45 ha) during the same period. Shrubs significantly showed an increasing trend of land use while forest areas are decreasing in area compared to other land use classes. Rapid land use change took place in the northern part of Gua Musang district whereby, nearly 36% of the changes was in terms of shrub, oil palm and rubber land use conversions. The method used and the results obtained strongly suggest that the integration of remote sensing and GIS offer very promising opportunities for land use change detection and mapping.